ANALISIS FASILITAS BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI KELAS XI IIS DI SMAN 1 TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Ahmad Ridho; Gimin Gimin; Hardisem Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to determine analysis of learning facilities and interest to learn on student learning outcomes in class XI in economics subject at selat panjang 1 senior high school. It’s using a quantitative descriptive approach, the population in the study as many as 80 students and the population was taken as sample (random sampling). Data collection technique using document and questionnaires. The analysis of data was used multiple regression. The result showed that the the learning facilities influences learning outcomes, and interest to learn influences learning outcomes.Key Words: Learning Facilities, Interest to Learn, Learning Outcomes